2012
DOI: 10.1111/j.1528-1167.2012.03586.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of people with epilepsy who attend emergency departments: Prospective study of metropolitan hospital attendees

Abstract: SUMMARYPurpose: One fifth of people with established epilepsy attend hospital emergency departments (EDs) and one half are admitted each year. These ED visits are not necessarily required, and unplanned hospitalizations are costly. Reducing avoidable ED visits and admissions is a target in most health services. The development of interventions is, however, challenging. Policymakers lack information about users' characteristics, factors associated with ED use, as well as quality of care. This study provides thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
74
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 55 publications
1
74
0
Order By: Relevance
“…10,11 16 further articles/sources which were considered relevant by the authors but not captured by the original search were also included. 4,[7][8][9][12][13][14][15][16][17][18][19][20][21]38,40 Articles referenced but not captured within the original search were used to complement the review and included those which highlight the scale of the problem, 4,7-9 papers which do not relate directly to pre-hospital services 10,[13][14][15][16][17][18]38,40 or seizure management itself 11,19,20 and one article on simple febrile seizures. 21 There is an extensive literature on the management of the seizure patient after arrival in the ED, however, this is beyond the scope of this review.…”
Section: Literature Review Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 16 further articles/sources which were considered relevant by the authors but not captured by the original search were also included. 4,[7][8][9][12][13][14][15][16][17][18][19][20][21]38,40 Articles referenced but not captured within the original search were used to complement the review and included those which highlight the scale of the problem, 4,7-9 papers which do not relate directly to pre-hospital services 10,[13][14][15][16][17][18]38,40 or seizure management itself 11,19,20 and one article on simple febrile seizures. 21 There is an extensive literature on the management of the seizure patient after arrival in the ED, however, this is beyond the scope of this review.…”
Section: Literature Review Methodsmentioning
confidence: 99%
“…6 Those who repeatedly attend EDs report poorer Quality of Life (QoL), increased stigmatisation and higher levels of anxiety and depression. 7 ED visits and subsequent hospitalisations contribute to the majority of the economic burden of uncontrolled epilepsy 8 with previous authors recently estimating an annual cost of s417,074 (£347,544) per 100,000 per year for hospital admissions alone. 9 In this paper we initially present a summary of the current official UK guidance for the pre-hospital management of seizures by ambulance clinicians.…”
mentioning
confidence: 99%
“…[5][6][7][8] People with epilepsy at high risk for frequent ED visits are an ideal target group for enrollment in programs to enhance outpatient care, because frequent ED use indicates poor access to care and/or poor disease control. [9][10][11][12] Quantifying "high risk" in this context is an active area of research. 13 Prior work using data from multiple hospitals found that future frequent ED use could be accurately predicted solely by examining prior ED use, despite the availability of additional demographics and comorbidity data.…”
Section: Introductionmentioning
confidence: 99%
“…10 For people with epilepsy, several factors are associated with frequent ED use: low socioeconomic status, more seizures, anxiety, poor knowledge of epilepsy by self or caregivers, and greater stigma. [11][12][13] However, the predictability of frequent ED use is understudied. Studying frequent ED use is challenging, in part because people often use multiple EDs for care.…”
mentioning
confidence: 99%